Cytogenetics of a new species of Paratelmatobius cardosoi group (Anura : Leptodactylidae), with the description of an apparent case of pericentric inversion - Lourenco, L. B.; Garcia, PCA; Recco-Pimentel, S. M. (Brill Academic Publishers, 2003)
The karyotype of a new species of Paratelmatobius from the P cardosoi group is described. As with other Paratelmatobius and Scythrophrys karyotypes, Paratelmatobius sp. (aff. cardosoi) shows a diploid number of 24 chromosomes, in addition to other similarities with the former karyotypes. The Paratelmatobius sp. (aff. cardosoi) karyotype differs from that of P. cardosoi in the morphology of pair 4, the NOR location and the C-bands in pairs 3 and 8 (exclusive to Paratelmatobius sp.) and those of pairs 7 and 9 (exclusive to P. cardosoi). Both karyotypes also differ in the amount of heterochromatin in pair 1. The presence of interstitial heterochromatin in the long arm of pair 1 and the interstitial C-bands in both arms of chromosome 5 are apparently synapomorphic characters of P. cardosoi and Paratelmatobius sp. (aff. cardosoi), since they are absent in the other Paratelmatobius and Scythrophrys karyotypes. In Paratelmatobius sp. (aff. cardosoi), the nucleolus organizer region is on the short arm of a small metacentric chromosome (pair 9), an arrangement similar to the NOR-bearing chromosome pair in the karyotype of P. poecilogaster and in karyotype 11 of Scythrophrys. A conspicuous heteromorphism unrelated to the sex determining mechanism was also observed and probably arose from a pericentric inversion.